Impact of Architectural Forms on Human PerceptionA Neurocognitive Experimentation - Pal, Abhijeet; Haq, Ammar Ul (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2024)
The form or shape of the built environment is fundamental to architectural design, but not many studies have shown the impact of different forms on the inhabitants’ consciousness. This study will investigate the neurological correlates of different interior forms on the perceivers’ affective state and the accompanying brain activity. There exists a measurable and predictable relationship between the effect of the architectural form of buildings on their users’ brain wave frequencies, and then their consciousness status. Leveraging Electroencephalography (EEG), we quantitatively capture brainwave patterns as participants navigate diverse architecturally designed spaces virtually. Key objective is the development of a scientific measuring tool, aiding architects and designers in creating spaces tailored to desired consciousness states for optimal user experience and well-being.